Acute kidney injury and sinus bradycardia associated with near-drowning - Kemeç, Zeki; Gürel, Ali (National Kidney Foundation of Ukraine, 2020)
Acute kidney injury (AKI) occurs in different situations and may have a variable prognosis due to underlying cause, clinical setting and comorbidity. Near-drowning is known to lead to bradycardic rhythms which can lead to hypoxia because of hypoperfusion. AKI has a high risk of mortality and morbidity. However, sequelae of sinus bradycardia are related to its underlying etiology. Urinary, cardiovascular and respiratory disorders are more frequently seen after near-drowning. Near-drowning related AKI and sinus bradycardia are not reported together in the literature. We aimed to emphasize these complications in near-drowning patients. © 2020, National Kidney Foundation of Ukraine. All rights reserved.
Keywords: acute kidney injury; Near-drowning; sinus bradycardia